Matching as a cure for underprovision of voluntary public good supply: Analysis and an example - Wolfgang Buchholz; Richard Cornes; Dirk Rübbelke (Center for Economic Studies and ifo Institute (CESifo), 2011)
Matching mechanisms are regarded as an important instrument to bring about Pareto optimal allocations in a public good economy and to cure the underprovision problem associated with private provision of public goods. The desired Pareto optimal interior matching equilibrium, however, emerges only under very special conditions. But we show in this note that corner solutions, in which some agents choose zero flat contributions, normally avoid underprovision and illustrate and interpret our results by a simple numerical example.
Keywords: C78; H41; 330; public goods; matching; Pareto optimality; Öffentliches Gut; Versorgung; Spieltheorie; Matching; Pareto-Optimum; Theorie